2013
DOI: 10.1620/tjem.230.205
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Carotid and Vertebral Rete Mirabile Presenting with Subarachnoid Hemorrhage Caused by the Rupture of Spinal Artery Aneurysm

Abstract: Rete mirabile (or carotid rete) is a normal structure that plays physiological roles in the lower mammals. However, the rete does not exist in the normal carotid circulation of humans. Carotid rete mirabile (CRM) is a rare condition compensating for congenital dysplastic internal carotid artery. Arterial plexus at the cavernous region, which supplies intradural internal carotid artery instead of the aplastic cavernous portion of internal carotid artery, looks like the "rete mirabile" seen in the lower mammals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…9) ASA aneurysms related to congenital anomalies of the VA are markedly rare. Only one case report on an ASA aneurysm related to vertebral rete mirabile was published by Nagahata et al 5) They reported the hemodynamic development/rupture of aneurysms of the anterior spinal arteries functioning as collateral pathways for bilateral vertebral retes , and emphasized that ASA aneurysms should be suspected when VA abnormalities are observed in the presence of non-typical subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9) ASA aneurysms related to congenital anomalies of the VA are markedly rare. Only one case report on an ASA aneurysm related to vertebral rete mirabile was published by Nagahata et al 5) They reported the hemodynamic development/rupture of aneurysms of the anterior spinal arteries functioning as collateral pathways for bilateral vertebral retes , and emphasized that ASA aneurysms should be suspected when VA abnormalities are observed in the presence of non-typical subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…1) Anterior spinal artery (ASA) aneurysms are complicated by vascular anomalies, 1) such as spinal arteriovenous anomalies and coarctation of the aorta, autoimmune disease, 2) angitis, 3) such as connective tissue disease or infection 4) in many cases, but only a few case reports on the rupture of an ASA aneurysm related to bilateral vertebral artery (VA) occlusion have been published. [5][6][7][8] In this study, we report a patient with subarachnoid hemorrhage in whom occlusion of the bilateral VA trunks and a right posterior inferior cerebellar artery (PICA)--anterior inferior cerebellar artery (AICA) anastomotic artery aneurysm were detected, and coil embolization was performed considering it to be the source of hemorrhage, but postoperative detailed examination suggested an ASA aneurysm as the source of hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…A ruptured cerebral aneurysm could be seen in half of these SAH cases, which were managed either by targeted endovascular methods or by surgical clipping. 11,12 Conservative management was adopted in the rest of the SAH cases in which aneurysm was not detected, and they were followed up with serial imaging for any interval development of aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…ASA aneurysms can be coiled in selected cases ( Figure 11 ) ( 116 , 117 ). However, due to the tortuous path and remote location, coiling is often difficult and impossible because EVT has a low likelihood of parent artery preservation with the latter option ( 118 ).…”
Section: Cervical Asa As a Collateral Channelmentioning
confidence: 99%